Study of Morphometric Analysis of Acetabulum and its Clinical Correlation - Ammara Ghafoor, Nadia Ahmad, Fauzia Siraj, Sumera Khalil, Nafeess Kiran, Tayyaba Fahad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgeon may learn more about the acetabular morphology and make a more accurate diagnosis of hip dysplasia by measuring the acetabular depth ratio. Understanding the intricacy and etiopathogenesis of illnesses like primary osteoarthritis of the hip joint etc. requires a thorough familiarity with the anatomical factors associated with this region. Objective: To evaluate the morphometric analysis of acetabulum and its clinical correlation. Study Design: Observational based study Study Setting: This study was conducted in Department of Anatomy, Sharif Medical and Dental College, Lahore from July 2022 to December 2022. Methodology: Using the teaching collection of the Anatomy Department, researchers examined 160 hip bones from adults with known sex. A set of digital vernier calipers was used to get all the measurements. Each variable was measured twice at separate times, and the mean of the two values was recorded. With no abnormalities in the morphology or moisture content of any of the chosen hip bones were included in the study. Osteoarthritic alterations, traumatic injuries, and skeletal diseases all led to specimen exclusion. SPSS version 20 was used for data analysis. Results: All anatomical parameters of 160 hip bones were calculated in cm in which 76 (47.5%) were males and 84 (52.5%) were females. There was no statistically significant difference between the right and left sides of anatomical parameter (p>0.05). However, there were statically different in between gender. Males had a deeper acetabulum (2.8 cm) than females (2.6 cm). The acetabular diameter was statistically significantly larger in men than in females (p=0.00). The notched width in females was larger (2.75 cm) than in men (1.75 cm), and the capacity was more in males as compared to female. 96.7% of the bones had a pointed front and a lunate-shaped back. The form of the lunate at both the anterior and posterior ends is present in 3.3% of the cases. Conclusion: In conclusion, by comparing male and female 20 to 47 years of age, the current research found statistically highly significant (p<0.05) differences in acetabular depth, diameter, capacity, and notch width. Ninety-three percent of the bones had a pointed front and a lunate-shaped rear. Just 5% of instances don’t have the lunate shape at either the anterior or posterior ends. In order for orthopedic surgeons to accurately determine the diameter of the acetabulum during surgical operations, it is required to do a preoperative evaluation of the acetabulum’s diameter. Keywords: Acetabulum Diameter, Acetabulum Depth, Acetabulum Width, Acetabulum Capacity